What is Effective in Massage Therapy? Well, “It Depends…”: a Qualitative Study of Experienced Orthopaedic Massage Therapists - Stewart-Richardson, Jennifer L.; Hopf, Suzanne C.; Crockett, Judith; Southwell, Phillipa (International Journal of Therapeutic Massage & Bodywork, 2024)
Background: Massage has been used as a treatment for musculoskeletal pain throughout history and across cultures, and yet most meta-analyses have only shown weak support for the efficacy of massage. There is a recognised need for more research in foundational questions including: how massage treatments are constructed; what therapists actually do within a treatment, including their clinical reasoning; and what role therapists play in determining the effectiveness of a massage treatment. Purpose: The aim of this study was to explore what experienced orthopaedic massage therapists consider to be the aspects of their work that contribute to effectiveness. Setting and Participants: Semi- structured interviews were conducted via Zoom with six experienced orthopaedic massage therapists in Australia. Research Design: The interviews were analysed using inductive thematic analysis, seeking insights that might be practically applied, rather than theory-driven interpretations. Results: The participants focused on the underlying differences between clients, between therapists, and between treatments, and clearly indicated that this concept of “difference” was foundational to their view of their work and was the underlying context for the comments they made. Within that frame of “difference”, three key themes were interpreted from the data: (1) “Everyone is different so every treatment is different”: how they individualised treatment based on these differences; (2) “How therapists cope with difference”: how they managed the challenges of working in this context; and (3) “What makes a difference”: the problem-solving processes they used to target each treatment to meeting the client’s needs. Conclusions: Participants did not identify specific techniques or modalities as “effective” or not. Rather, a therapist’s ability to provide effective treatment was based on an iterative process of treatment and assessment that allowed them to focus on the individual needs of the client. In this case “effectiveness” could be considered a process rather than a specific massage technique.